(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes the interrelation and harmony of moral and aesthetic values, which are essential components of personal development. The significance of moral norms in shaping human behavior and social relations, as well as the role of aesthetic perception and artistic taste in enriching an individual’s inner world, is examined. The article discusses how these two systems of values complement one another and their synergistic impact on forming a well-rounded personality from philosophical and cultural perspectives.